Seagrass ecosystems in Pujada bay, Davao Oriental, Philippines: evaluating the impact of anthropogenic pressures on species richness - Sanchez-Delute, Claudine C.; Edgar B. Atoy, Sherwin; Ybañez Jr, Cirilo O. (Academia Journal of Biology, 2025)
This study investigates the biodiversity of seagrass ecosystems in Pujada Bay, Davao Oriental, Philippines, with a particular focus on evaluating the impact of anthropogenic pressures on species richness and composition. Seagrass communities from three sites with varying disturbance levels were compared: heavily populated Taganilao, moderately populated Lawigan, and uninhabited Pujada Island. Aerial surveys, transect-quadrat sampling, and environmental measurements (dissolved oxygen (DO), pH, salinity, temperature) were used to assess species distribution, shoot density, and abundance. Results showed that Pujada Island had the highest species richness and a balanced community structure, while Taganilao, impacted by pollution and reclamation, had lower diversity and was dominated by the resilient Thalassia hemprichii. Kruskal-Wallis tests confirmed significant differences in abundance, especially between Taganilao and Pujada Island (p = 0.000273). Canonical Correspondence Analysis highlighted temperature and DO as key drivers of species distribution. The study underscores the urgent need for conservation measures to mitigate human impacts and protect seagrass ecosystems in Pujada Bay.